Self-healing cement materials – microscopic techniques - Dudek, Marta (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
The article presents a general classification of intelligent materials with self-healing (self-repairing) properties, focusing on self-healing cementitious materials. The purpose of the paper is to describe the prospects of two of the most popular micro-observation techniques, i.e. with the use of an optical and scanning electron microscope. In addition, it describes the advantages of using a tensile stage mounted in the microscope chamber for testing self-healing materials. The advantages and disadvantages of these devices have been characterized, and the results of preliminary research have been provided. The tests include the optical microscopy and scanning electron microscopy observations of the microstructure of cracks before and after the process of healing. They were carried out using ZEISS Discovery V20 optical microscope and ZEISS EVO-MA 10 scanning electron microscope on mortar samples modified with macro capsules filled with polymer. In addition to observations, chemical analysis was performed with the use of an EDS detector. The microscopic observations and chemical analyses provide the basis for assessing the effectiveness of the self-healing process, showing that the crack has been healed. Moreover, the preliminary results of the tests of micro-mechanical properties, carried out with the use of a tensile stage, have been described. The problems of using this research technique are also listed. This study shows the usefulness of this kind of tests for microcapsules for self-healing materials.